2022
DOI: 10.1097/gox.0000000000004637
|View full text |Cite
|
Sign up to set email alerts
|

Does Fitzpatrick Score Predict Flap Loss? Microsurgical Breast Reconstruction Outcomes of Varying Skin Color

Abstract: Background: The aim of this study was to seek evidence that patients with darker Fitzpatrick score skin tones are more susceptible to flap loss due to unsalvaged vascular compromise in autologous flap breast reconstruction. Methods: This is a retrospective study conducted on patients who underwent any type of autologous flap breast reconstruction performed by the two senior authors at an academic center between January 2010 and December 2021. The sole p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…Nursing staff have reported preferring the binary outcome of whether flow is present or not compared to the subjective assessment of skin paddles [ 11 ]. A subjective assessment of skin paddles can be challenging in non-Caucasian skin and, as such, is associated with a higher incidence of flap loss due to delayed flap salvage [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…Nursing staff have reported preferring the binary outcome of whether flow is present or not compared to the subjective assessment of skin paddles [ 11 ]. A subjective assessment of skin paddles can be challenging in non-Caucasian skin and, as such, is associated with a higher incidence of flap loss due to delayed flap salvage [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…Existing research on skin color in the field of plastic surgery has shown that it can be an important factor not only in health equity but also in the prevalence of disease, patient risk for certain conditions, and patient outcomes, 2,[16][17][18] but such investigations are hindered by difficulty collecting objective and consistent data on skin color. It has been reported that plastic surgery journals use significantly more images of white-skinned than dark-skinned individuals.…”
Section: Discussionmentioning
confidence: 99%
“…For example, one study found that patients with darker FST are more likely to experience flap loss following autologous flap breast reconstruction, potentially due to providers’ inability to notice skin changes in patients with darker FST. 2 …”
mentioning
confidence: 99%
“…For example, one study found that patients with darker FST are more likely to experience flap loss following autologous flap breast reconstruction, potentially due to providers' inability to notice skin changes in patients with darker FST. 2 Effectively measuring skin tone is vital to conducting health disparities research and improving surgical outcomes. Given the difficulty of recording racial data in electronic health records, FST has become a commonly used proxy for race/ethnicity.…”
mentioning
confidence: 99%